Energy-Economy Nexus in Indonesia: A Bivariate Cointegration Analysis - SOILE, Ismail O (Asian Journal of Empirical Research, 2012)
Inefficient pricing of energy products has become common feature of governments in many oil exporting developing countries. As developing countries, this can be justified only when the increased growth results from such higher energy consumption. To this end, the study examined the direction of causality between energy consumption and economic growth, and the possibility of a long run relationship between the two variables using Indonesia’s time series for the period of 1971-2010. The Granger causality test revealed a unidirectional causation running from economic growth to energy consumption, and the existence of a long run relationship. The study therefore suggests the pursuance of major reforms to ensure appropriate pricing of energy products. This can help checkmate excessive consumption with no devastating harm to economic growth.